Pengembangan Ensiklopedia Alat Ukur Fisika sebagai Sumber Belajar untuk Siswa SMP/MTs - Isfaul Maulina; Hamdan Hadi Kusuma; Muhammad Izzatul Faqih (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
This research aims to produce a product in the form of an encyclopedia of physics measuring instruments and to find out the quality of the encyclopedia of physics measuring instruments as a learning resource for SMP / MTs students. The type of research used in this research is Research and Development (RD), referring to the development of Borg Gall which has been modified by Sugiyono. The subjects of this study were students of class VII SMP Negeri 1 Brangsong. Data collection techniques in this study were carried out by means of interviews and questionnaires. The results of the encyclopedia quality assessment based on the evaluation of material experts are 100% with very good category, media experts are 94.29% with very good category, assessment from science teachers is 93.33% with very good category, and the assessment of student responses in the small-scale trial was 97.78% with the very good category. Based on this assessment, it can be concluded that the encyclopedia of physics measuring instruments developed has very good quality and is suitable for use as a learning resource for SMP / MTs students.